The Social Poetics of the Red River Jig in Alberta and Beyond: Meaningful Heritage and Emerging Performance - Quick, Sarah (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2008)
AbstractThe Red River Jig is a fiddle tune and a dance form that have particular resonance for First Nations and Métis peoples in Northern and Western Canada. Here I follow the dance form’s practice across diverse settings in time and space. This article is a part of a larger project in which I am analyzing the nexus of Métis identity, performance, and heritage; using Michael Herzfeld’s concept of “social poetics” (2005) to gauge the Red River Jig not only as a representative form of Métis heritage, but as a performative form that emerges in social interaction. Here I first chronicle its performance through time and then describe its form and manners of learning this form in contemporary contexts in Alberta and Western Canada more generally. Finally, I examine the Red River Jig, or aspects of the Red River Jig, emerging in other dance forms as well as other performative circumstances beyond the categorical boundaries of music and dance to consider the social poetics of the Red River Jig within greater spheres of practice.